Tax Policy, Venture Capital, and Entrepreneurship. - Christian Keuschnigg; Søren Bo Nielsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
The paper studies the effects of tax policy on venture capital activity. Entrepreneurs pursue a single high risk project each but have no own resources. Financiers provide equity finance. They must structure the entrepreneur's profit share and base salary to assure their incentives for full effort. In addition to providing equity finance, venture capitalists assist with valuable business advice to enhance survival rates. Within a general equilibrium framework with a traditional and an entrepreneurial sector, the paper investigates the effects of taxes on the equilibrium level of entrepreneurship and managerial advice. It considers differential wage and capital income taxes, a comprehensive income tax, incomplete loss offset, progressive taxation as well as investment and output subsidies to the entrepreneurial sector.
Keywords: 330